The relevance of sustainable development principles and goals through a case study of Gold Fields and Living Gold,An exploration of contextual implications of sustainable development and its prevailing applications for South African mining industries - the balanced bottom line - Ferreira, Adrian (Rhodes University, Faculty of Commerce, Investec Business School, 2007)
The conventional definition of sustainable development as proposed by the Brundtland Report (United Nations, 1987), involving the integration of economic, social and environmental components, is widely accepted. Presumed benefits of these current framework applications tend to perpetuate a business as usual status, with no real sustainable development occurring. The growing debate surrounding this topic makes the case for relevant and contextual inputs to be included into sustainable development objectives. A case study, of Gold Fields and Living Gold, attempts to create a deeper understanding of the components of this debate, and begins to contextualise sustainable development principles, goals and their outcomes. This is carried out though an enquiry of the use of cultural development as a fourth sustainable development category. The case study includes the opinions of a directly affected local community entity (Living Gold) in order to observe the difference between the two organisations (Gold Fields and Living Gold). During the study, the focus began to move away from purely unabated growth impacts and looked to the creation and fostering of resilience and flexibility by the use of adaptive management. In breeding states of resilience, it was recognised that cultural impacts played an important role in ensuring long term systemic resilience. The case study involved assessing the feedback and responses of strategically selected individuals at both organisations, with Gold Fields representing a more western centric entity and Living Gold a formal representation of a traditional/ indigenous community. Similarities and differences were assessed in order to understand how current sustainable development criteria might differ between organisations that have different end objectives in mind, yet are dependent on each other. The findings resulted in a perspective of how culture could be used to describe the qualities of a local community, and how to begin aligning development goals with affected communities. The result was the development of the Integrated Resilience Sustainability Method and the consequent development of the Balanced Bottom Line Framework, which seeks to promote sustainable development along the lines of economic, social, environmental and cultural development.
Keywords: Uncatalogued